Fair Use Copyright Intellectual Property Law Oracle vs Google Case Study - Yulio Iqbal cahyo Arsetyo (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Intellectual property (IP) is a kind of intellectual property that has been remarkably difficult to classify as a specific form of IP subject matter because its dual nature presents particular difficulties for those trying to draw analogies with existing legal categories. With the development of technology there was a new challenge for Intellectual property concept and it was about position of software in the world of intellectual Property. With now era of technology begin, there was new legal issue regarding intellectual property was rises. This case will inloved how google use Oracle copyrighted material the Java programing language especially the regarding the Application programming interface which created a 9 year long legal battle. From the back story this case actually was reveal that Google loan some of Java program Asset to uses in the Google Android Development Kits especially the API. By means of observing, studying and testing the behavior of SAS Institute's program, WPL reproduced the functionality of that program by using the same programming language and the same format of data files.